PERLINDUNGAN HUKUM ATAS HAK PEKERJA DALAM PERJANJIAN KONTRAK KERJA - Zhafirah, Talitha; Mardijono, H.R. Adianto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Wages are rewards or payments that are the rights of workers/laborers and an obligation for companies/employers. Several forms of wages take the form of daily hhwages, mmpiece wages, fixedbb wagesnn, non-fixednnwages provided by the company/employer to provide such compensation based on time and effort, performance, work performance, or services rendered by the worker/laborer. The right of workers/laborers to wages has legal protection. If wages are not paid or are paid lower than the Minimum Wage, the worker/laborer has the right to demand to be paid in accordance with the provisions of the minimum wage. Companies/employers who do not fulfill their obligations to pay appropriate wages/salaries will be subject to legal sanctions. Law enforcement on the payment of wages has been clearly regulated in Law Number 32 of 2003 concerning Manpower. The purpose of this writing is to understand the legal regulations regarding wages which are the rights of workers/laborers and the obligations of companies/employers. Using a normative juridical research method, which examines statutory regulations, legal definitions, or legal doctrines in order to answer legal problems or issues raised in this writing